Effectiveness of Xylene and Mineral Oil in DNA Extraction from Formalin-fixed Paraffin-embedded Diffuse Astrocytic Tumor - Edward Jaya Hadi; Hasrayati Agustina; Hermin Aminah Usman (Poltekkes Kemenkes Banjarmasin Jurusan Analis Kesehatan, 2022)
Formalin-fixed paraffin-embedded (FFPE) tissue is an important source of material for molecular analysis. In the anatomical pathology field, molecular testing is needed in certain tumors, such as astrocytic tumors, to confirm the diagnosis. Extracting DNA from FFPE material is still challenging. The first important step in the extraction process is deparaffinization. This study aims to compare two types of deparaffinization methods. The first method used xylene, and the second one used mineral oil. The results of this study can be used to develop a reliable protocol for DNA extraction from FFPE tissue. DNA from 28 FFPE diffuse astrocytic tumor tissue blocks was extracted. The quantity and A260/A280 ratio of the DNA was measured by spectrophotometer. PCR assays were performed to assess the suitability of extracted DNA for molecular analysis. The results showed that the xylene group has significantly higher DNA concentrations than the mineral oil group (p<0.01). In both groups, average and median A260/A280 scores were between 1.8-2.0. In PCR assay, both groups show a similar result (27 of 28 samples were successfully amplified). In conclusion, xylene and mineral oil can be used effectively as deparaffinization agents. Both methods generated good quality extracted DNA. The advantage of mineral oil is that it is non-toxic and has shorter hands-on time. Xylene is preferable for a small-sized sample because it produces a higher DNA yield.